The Role of Artificial Intelligence Tools and Digital Literacy in Shaping EFL Students' English Writing Skills - Billy Ar Rusdi Askar (Greenation Education and Culture Review, 2025)
The rapid development of digital technology, particularly Artificial Intelligence (AI), has brought significant changes to English as a foreign language (EFL) learning, especially in writing skills. This article aims to conceptually examine the role of Artificial Intelligence tools and digital literacy in shaping EFL students' English writing skills. This study uses a conceptual review approach with a literature review method of scientific articles, books, and research reports relevant to writing learning, educational technology, and digital literacy. The results of the study show that the use of AI tools, such as grammar correction applications, machine-assisted writing, and automatic feedback, can help students improve linguistic accuracy, text organization, and metacognitive awareness in writing. However, the effectiveness of AI tools depends heavily on students' digital literacy, which includes the ability to understand, evaluate, and use technology critically and ethically. Digital literacy plays an important role in ensuring that the use of AI is not merely mechanical but also supports the development of critical thinking and creativity in writing. This article emphasizes that the balanced integration of AI tools and digital literacy can be a potential strategy for improving the quality of EFL writing instruction. These conceptual findings are expected to serve as a basis for educators and researchers in designing more effective technology-based writing instruction that is oriented toward the development of 21st-century competencies.